ABSES TUBERKULOSA OTAK PADA REMAJA DENGAN HIV NEGATIF - Mayo Djitro,* Yanto Budiman,*,** Ronny *,** (Neurona Majalah Kedokteran Neuro Sains, 2020)
IS HIGHLY PREVALENT IN DEVELOPING COUNTRIES IT IS MOST COMMONLY SEEN INFECTING THE LUNGS BUT CAN ALSO BE FOUND AS EXTRAPULMONARY TUBERCULOSIS EPTB CENTRAL NERVOUS SYSTEM CNS TUBERCULOSIS REPRESENTED ABOUT 10 OF EPTB THE PRIMARY FORM OF CNS TB IS MENINGITIS TB THERE ARE HOWEVER OTHER RARER FORMS SUCH AS TUBERCULOUS BRAIN ABSCESS TBA ABSCESSES ARE MORE COMMONLY SEEN IN IMMUNOCOMPROMISED PATIENTS